Kemampuan Matematika Permulaan Anak Usia 5-6 Tahun - Hasnur, Reyzia Anggriani; Maghfirah, Febry; Kartika, Wilda Isna (Jurnal Ilmiah Potensia, 2025)
This study aims to describe the mathematical abilities of 5-6-year-old children in kindergartens across Samarinda Ulu Subdistrict. The 2018 and 2022 PISA results indicate that Indonesia's mathematical abilities are still below the global average (around 500) (L. Sulistyo & Dwidayati, 2021). This problem is also found in several kindergartens in Samarinda Ulu Subdistrict, with some teachers reporting difficulties in students' ability to sequence numbers 1 through 20. This study uses a quantitative approach with a survey research design. Data were collected through questionnaires given to kindergarten teachers who teach 5-6-year-old children (Group B) in Samarinda Ulu Subdistrict. The number of participants in this study was 100 children. Data analysis was performed using SPSS version 22.0. The results showed that the early mathematical abilities of 5-6-year-old children in Samarinda Ulu Subdistrict still need to be improved. The average score of children's abilities on the 22 items observed was 2.01, which indicates that children's abilities are still in the "Beginning to Develop" stage. Specifically, children's abilities in mentioning numbers 1-20 (average score: 2.03), counting the number of objects in the picture (average score: 1.85), and showing numbers (average score: 2.1) are also still in the "Beginning to Develop" stage. This questionnaire includes questions about number recognition, simple addition, and other basic math concepts. This study has limitations, including a relatively small sample size and reliance on teacher reports. The implication of this research is the need for early intervention to improve the mathematical abilities of children in Samarinda Ulu Subdistrict, especially in arithmetic and number recognition skills.